RACISM IN THE FREEDOM WRITERS MOVIE BY RICHARD LAGRAVENESE: A CRITICAL DISCOURSE ANALYSIS PERSPECTIVE - Siti Nurrotul Aini; Joko Wibowo (English Language Teaching Journal, 2024)
Abstract Racism is not the strange topic anymore for the people worldwide. The idea of racism is the exclusion of a group of individuals according to their race or ethnicity. One of the movies that raised this theme is The Freedom Writers. This movie is an American biographical drama movie written and directed by Richard LaGravenese in 2007. This study will identify racism using Van Dijk's Critical Discourse Analysis theory in the text dimension as reflected in The Freedom Writers movie. This study is a descriptive qualitative approach using Teun A. Van Dijk's Critical Discourse Analysis and only focus on text dimension (Macro Structure, Superstructure, and Microstructure). The main theme in the movie is the struggle against racism through education with the sub-theme of education as a tool of social change, highlighting Erin Gruwell's efforts to overcome racial divisions in her classroom through innovative teaching methods. The movie's structure begins with exposition, rising action, climax, falling action, and resolution that illustrate the challenges and successes in changing attitudes and promoting inclusivity in Erin's classroom. In this study, 11 texts in the scenes were found to contain elements of racism such as racial discrimination and systemic injustice, structural racism, negative stereotyping, and ignorance of context. Racism can cause traumatizing, violent effects on individuals, anger and irritation, and others. Keywords: Racism, Education, The Freedom Writers Movie, Van Dijk’s CDA